Analysis of the implementation of mediation as an alternative dispute resolution method in the Latvian legal system - Lagzdiņš, Deniss (Riga Graduate School of Law, 2021)
Optimisation of dispute resolution within European Union Member States is an ongoing trend in order to facilitate access to justice for individuals. In Latvia, the integration of the Mediation Law was a step towards further developments in increasing the efficiency of the justice system. However, the implementation mechanisms are as important as integration of mediation at a regulatory level. The overarching goals of developing Alternative Dispute Resolution methods within a state’s legal system facilitate access to justice with a society ready and determined to pursue the utilitarian value of dispute resolution outside of court systems. This paper discusses the effect of integration of mediation within the Latvian legal sphere at a regulatory and implementation mechanism context.
Keywords: Alternative dispute regulation; Mediation; Latvia